Musik Dan Trance: Studi Kasus Seni Pertunjukan Jaranan “Turangga Muda Budaya” Tulungagung, Jawa Timur - Septiya, Marenda Adhi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
Jaranan is a synthesis art between music and dancing in wich has a value of ritual. there is a diffrence between jaranan art and the others art. in the jaranan art, the actor experinces trance or in java language called "nadadi". The research is to find Sind out and to explains about the relation of music and trance in jaranan art. based on the previous finding done by Kartomi and groenendeal can be known that music that has high pitch and monotonous rhytem can couse dancers fall into trance condition.this is all qualitative research with approach of case study. The object of the research in group of jaranan art. "Turangga Muda Budaya” basides that, this research also is supported by Reuget's concept on music ad trance, Beker concept and response of emotion as well as Meyer's concept on music and emotion. from the research is finded that trance condition that the dancer experience will be happen when the such dancers listen to music of accompanist of jaranan. The music cosist of some instruments such slompret and ketuk kenong.These instruments can cause arise extrime pleasure that the real manifestation of it is trance.